Managerial Leadership: X-Ray Of Issues And Facts - Ajila, C.O.; Ibukun, C. O. (Advances in Social Sciences Research Journal, 2019)
Managerial leadership pervades the theory and practice of work organizations. It integrates the characteristics of a good leader and the expertise and competence of a manager. Thus, amalgamating and advocating the functions assumed by managers and leaders for efficient task performance and organizational productiveness. This paper x-rays issues in Managerial Leadership, differences between management and leadership/manager versus leader. It further presents managerial leadership bases of power, meaning of managerial leadership, skills that are essential for facilitating better managerial leadership, forces in deciding how to lead, levels of managerial leadership participation and concludes with suggestions for managerial leadership effectiveness.